2022
DOI: 10.1590/1519-6984.237869
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive diseases in captive Agoutis (Dasyprocta leporina)

Abstract: Reproductive diseases have been well documented in domestic livestock such as sheep, goat, cattle and pigs. However, there is very little information on these diseases in the agouti (Dasyprocta leporina). The agouti is used for its meat in South America and the Caribbean. More recently, intensive farming of this animal is being practiced in the Neotropics. There is dearth of information on dystocia and vaginal prolapses in the agouti. This document reports on three cases of reproductive diseases in captive rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In most cases, the agouti serves as a reservoir host for a variety of diseases without showing any clinical signs. Some of the associated organisms are Toxoplasma gondii [25][26][27], Leishmania spp. [28,29], Trypanosoma cruzi [30,31], and Echinococcus oligarthrus [32].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the agouti serves as a reservoir host for a variety of diseases without showing any clinical signs. Some of the associated organisms are Toxoplasma gondii [25][26][27], Leishmania spp. [28,29], Trypanosoma cruzi [30,31], and Echinococcus oligarthrus [32].…”
Section: Discussionmentioning
confidence: 99%
“…Agoutis ( Dasyprocta spp.) are medium-sized rodents that weigh between 2–3.5 kg [ 13 , 14 , 15 , 16 , 17 ]. Studies defining the age of puberty in females are lacking, however, Guimarães et al [ 18 ] showed that, under the male effect, puberty in D. prymnolopha was attained at nine months.…”
Section: Introductionmentioning
confidence: 99%